Effects of climate on fatty acid profile in Camelina sativa - Raziei, Zahra; Kahrizi, Danial; Rostami-Ahmadvandi, Hosein (Cellular and Molecular Biology, 2018)
Due to the importance of Camelina for low expectation (water and other inputs) and as an oil crop, Soheil cultivar was cultivated in Ardebil, Hamedan, Rasht, Ilam, Kermanshah, Karaj, Mashhad, Ahvaz and Bushehr Provinces. Fatty acids were measured with MG-Mass. Results showed that morphological traits were not very dependent on the climate, but the profile of the fatty acids was dependent. ANOVA of the effects of climate on the saturated fatty acid showed that there were significant differences between climates for all studied SFAs (P<0.01) with the exception of Lauric acid. Mean squares of the effects of climate on the Unsaturated Fatty Acids (MUFA) in showing that there were significant differences between climates for all studied MUFAs (P<0.01). Mean squares of the effects of climate on the amount of polyunsaturated fatty acids (PUFA), oil percentage and protein content of seeds indicated that there were significant differences between climates for all these studied traits. Mean squares of the effects of climate on the amount of polyunsaturated fatty acids (PUFA), oil percentage and protein content of seeds indicated that there were significant differences between climates for all these studied traits. The statistical analysis for the effects of Climate on the ratio of the Saturated Fatty Acid (SFA) in Camelina sativa showed that there were significant differences (P<0.01) for SFA, MUSFA, PUFA, MP, P:S and MP:S. Briefly, in the cold climates, the percentage of unsaturated fatty acids was higher. So it is possible to the cultivation of this plant in cold provinces for nutritional purposes and in tropical provinces for industrial and sanitary purposes.